THE MYTH ANALYSIS IN DEMAIN DES L’AUBE POETRY BY VICTOR HUGO - Yulia Sofiani Zaimar; Leni Tiwiyanti; Yosi Maeleona Passandaran (Sekolah Tinggi Bahasa Asing LIA, 2022)
A poem is able to construct and represent various events, that relates in people's lives, such as people's habits, family life, married life, history and so on. Poetry is an expression that is dense, concise and full of meaning. Poetry has a characteristic that is using short sentences and consists of only three stanzas. In poetry, there are many expressions of expression that are expressed indirectly so that it requires deeper meaning. Each poem certainly has different characteristics in packaging and representing issues and themes that will be raised into a story according to the ideology and goals to be achieved by the author. This research would like to research Victor Hugo’s poem, titled Demain dès l’aube. The purpose of this study is to reveal the semiotics of signs. This research aims to find out the signifier, signified, and myth in the poem by Victor Hugo, through the relationship between father and daughter. This study uses a qualitative method, combined with the Roland Barthes’ semiotics theory. As the result, this poem told about a person, who lost his daughter. Secondly, this poem is a true story of Victor Hugo, him-self, when his daughter died. The signifier and the signified found in this research represent the father's love for the child in the poem, signed by the broken feelings of the father, who was unable to save his lovely daughter Keywords: Poem, Hugo, Father, Semiotic and Myth Abstrak Sebuah puisi mampu mengkonstruksi dan merepresentasikan berbagai peristiwa, yang berhubungan dalam kehidupan masyarakat, seperti kebiasaan masyarakat, kehidupan keluarga, kehidupan pernikahan, sejarah dan sebagainya. Puisi merupakan ungkapan yang padat, padat dan penuh makna. Puisi memiliki ciri khas yaitu menggunakan kalimat-kalimat pendek dan hanya terdiri dari tiga bait. Dalam puisi banyak sekali ungkapan ungkapan yang diungkapkan secara tidak langsung sehingga membutuhkan makna yang lebih dalam. Setiap puisi tentunya memiliki ciri khas yang berbeda dalam mengemas dan merepresentasikan isu dan tema yang akan diangkat menjadi sebuah cerita sesuai dengan ideologi dan tujuan yang ingin dicapai oleh pengarangnya. Penelitian ini ingin meneliti puisi Victor Hugo yang berjudul Demain dès l’aube. Tujuan dari penelitian ini adalah untuk mengungkap semiotika tanda. Penelitian ini bertujuan untuk mengetahui penanda, petanda, dan mitos dalam puisi karya Victor Hugo, melalui hubungan antara ayah dan anak perempuan. Penelitian ini menggunakan metode kualitatif yang dipadukan dengan teori semiotika Roland Barthes. Alhasil, puisi ini menceritakan tentang seseorang yang kehilangan putrinya. Kedua, puisi ini adalah kisah nyata Victor Hugo, dirinya sendiri, ketika putrinya meninggal. Penanda dan petanda yang ditemukan dalam penelitian ini merepresentasikan cinta ayah kepada anak dalam puisi tersebut, ditandai dengan hancurnya perasaan ayah yang tidak mampu menyelamatkan putri kesayangannya Kata kunci: Puisi, Hugo, Ayah, Semiotika dan Mitos